Casa Cunhã Moaçara: um espaço de apoio a cultura popular em Belterra/PA - Cruz, João Pedro Rocha da (Brasil, 2022)
The current work aims to develop a catalyst-agent-space of local culture in Belterra, a small town in Amazon, conceived to respond the local folklore groups demand for a public equipment of artistic production and fruition. The architectural proposal has the intention to ensure the expression and maturing of young artists while keep cultural traditions alive, certifying the right of cultural production and being a stage for narratives of native peoples and their perspectives. The house contemplates ateliers for visual arts, rooms for per forming arts, scenical space for performances and others spaces of support to attend secondy activities.